Penerapan Struktur Naratif Tiga Babak dalam Penulisan Naskah Video Feature “Setu Babakan: Rumah Betawi Hari Ini” - Siti Noorhayati Fajriani; Ridha Elsarah Affendi; Encang Saepudin; Kurnia Lucky Fadillah (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
The existence of Betawi traditional houses amid the rapid modernization of Jakarta has indicated a shift in their function from residential spaces to symbols of cultural preservation. This condition encouraged the creation of the video feature entitled “Setu Babakan: Rumah Betawi Hari Ini” through the implementation of the three-act narrative structure in scriptwriting. This final project report aimed to describe the role of the scriptwriter in applying the three-act narrative structure during the creation process. A descriptive approach was employed by systematically explaining the pre-production, production, and post-production stages based on the creative experience. During pre-production, the scriptwriter conducted research, developed the concept, wrote the script, and prepared interview questions. The implementation of the three-act structure was reflected in the first act, which introduced Setu Babakan as a center of Betawi cultural preservation; the second act, which explored the history, architectural forms, and cultural values of Betawi traditional houses; and the third act, which presented reflections and expectations regarding the continuity of Betawi culture in modern society. During production and post-production, the scriptwriter ensured that all audiovisual elements remained aligned with the predetermined narrative structure. It was concluded that the implementation of the three-act narrative structure assisted the script writer in organizing cultural research findings into a coherent and communicative storyline that effectively conveyed cultural messages to the audience.